Synergy of ferroelectric-relaxor transition and multiphase coexistence induced high electrocaloric effect with wide temperature span in Pb0.7Ba0.3ZrO3-based system. (1st July 2022) - Liu, Wei; Li, Feng; Chen, Guohua; Li, Guohui; Zhai, Jiwei; Long, Mingsheng; Wang, Chunchang; Shan, Lei
Abstract: In this work, (1- x )Pb0.7 Ba0.3 ZrO3 – x Bi(Mg0.5 Ti0.5 )O3 (PBZ– x BMT) compositions was designed with an integration of ferroelectric–relaxor transition and multiphase coexistence to synergistically optimize electrocaloric effect (ECE) and temperature stability. Rietveld refinements reveal a phase structure change with sequence of R3cH  →  R3cH  +  Pm 3 ¯ m  →  Pm 3 ¯ m as BMT content increases, whilst relaxation property also increases with downshift in ferroelectric–relaxor transition temperature. Structural evolution is also verified by in-situ Raman spectra and ferroelectric measurements. Interestingly, a large ECE (Δ T ∼ 0.86 K) with a broad temperature span (Δ T span ∼ 58 K) was successfully obtained in x =0.01 composition, which is believed to be contributed by diffuse phase transition character with multiphase coexistence. This work provides a guideline to exploring ferroelectric materials with high ECE/wide operation span and the reported PBZ–based ceramics with a large Δ T and Δ T span is a promising candidate in application of solid–state cooling devices. Graphical abstract: Image, graphical abstract .